Neoadjuvant anti-PD-1-based immunotherapy: evolving a new standard of care - Drew M Pardoll; Suzanne L Topalian (Journal for ImmunoTherapy of Cancer)
Neoadjuvant (presurgical) anti-programmed cell death protein-1 (PD-1)-based immunotherapy as a new approach to cancer treatment has been developing on an accelerated trajectory since the seminal clinical trial results from studies in lung cancer and melanoma were published in 2018. Groundbreaking regulatory approvals in triple-negative breast cancer, non-small cell lung cancer and melanoma will certainly be followed by additional approvals in other disease indications, as clinical and basic research are burgeoning globally in hundreds of clinical trials across dozens of cancer types. As this field is evolving, it is addressing gaps in our understanding of biological mechanisms underlying PD-1 pathway blockade and their synergy with other antineoplastic drugs, probing mechanisms of response and resistance to neoadjuvant immunotherapy, optimizing efficacious clinical strategies, and analyzing commonalities and differences across cancer types. Knowledge gained thus far provides a firm foundation from which to launch the next phase of translational research in this expanding arena of biomedical investigation.